On the current agile assessment methods and approaches - Nafchi, Mina Ziaei; Zulzalil, Hazura; Gandomani, Taghi Javdani (IEEE, 2014)
Agile methods are widely used in software companies in recent years. Many software companies are replacing their traditional development methods with Agile methods. Nonetheless, measuring agility that they have achieved has be topic of debate. So far, only a few methods and tools have been proposed to measure the agility of software companies who are moving to agile. The main aim of this paper is reviewing the existing agile assessment methods and providing a brief discussion on drawbacks of these methods. This paper tries to elucidate the actual position of these methods in measuring agility degree of companies who are moving to agile approach.